Privy by the Bay: Emerging hotspot analysis of 311 reports of human/animal waste near San Francisco Pit Stop locations, 2009–2022 - Cari A. Bogulski; William P. Watson; Sean G. Young (PLoS ONE, 2025)
Access to basic sanitation facilities is a significant challenge for homeless populations, and evidence on the effectiveness of interventions to address this issue are still limited. San Francisco, California, has a large population of people experiencing homelessness and limited public restrooms. To increase access to public restrooms among this population in the city, the Pit Stop Program launched in 2014, introducing clean and safe public restrooms to high-need areas. This study built upon prior Pit Stop Program evaluations by conducting an Emerging Hot Spot Analysis (EHSA) using ArcGIS Pro v3.1.1 of human/animal waste reports across San Francisco to the city’s 311 system using spatial and temporal characteristics, and examined the presence of these hotspots among San Francisco neighborhoods. We examined 5,940,667 reports to 311 in conjunction with Pit Stop and public restroom locations. Waste reports in San Francisco showed an upward trend from 2009 to 2022, reaching an all-time high in 2022. Pit Stop Program sites were generally concentrated in areas with the most waste reports, particularly the Tenderloin and Mission neighborhoods. Spatiotemporal hot spots were identified throughout the city. Locations containing Pit Stops were more likely to be classified as diminishing hot spots. There is evidence of improvement in the Tenderloin neighborhood, which has seen the longest and most concentrated Pit Stop intervention, however the effect appears to be small. The findings suggest the need for additional research and continued efforts to address sanitation issues for people experiencing homelessness.